Management Practices Of Pelvic Inflammatory Disease In Lahore (Journal of Rashid Latif Medical College, 2025)
Background: Pelvic Inflammatory Disease (PID) is a serious reproductive health disorder that can cause chronic pelvic pain, ectopic pregnancy, and infertility if not well managed. Despite the guidelines for treatment, differences in diagnosis and management continue to exist in different healthcare facilities.Objective: To evaluate the existing practices of diagnosing and managing PID among clinicians working at the Avicenna Medical College Hospital and assess compliance with international treatment guidelines.Methodology: A cross-sectional quantitative descriptive study was done from January to June 2024 in the Department of Obstetrics and Gynecology. Data were gathered using a structured questionnaire administered among 80 clinicians, which consisted of postgraduate residents and consultants. Diagnostic techniques, antibiotic protocols, hospitalization indications, and follow-up strategies were evaluated through the questionnaire. Data were analyzed with SPSS v26. Descriptive statistics (means, frequencies, SD) and chi-square tests were utilized to establish association between clinician experience and guideline compliance.Results: 65 out of 80 participants responded with complete questionnaires (81.2%). Only 58.5% made use of standardized PID diagnostic criteria (cervical motion tenderness, pelvic tenderness, adnexal tenderness). The most commonly used regimen was ceftriaxone with doxycycline ± metronidazole (73.8%), in accordance with CDC recommendations. Still, 26.2% reported broad-spectrum antibiotic use outside guidelines. Consultants demonstrated significantly higher compliance with treatment protocols compared to residents (p=0.03). Follow-up within 72 hours was adhered to by 61.5% of clinicians.Conclusion: Although the majority of clinicians at the University Teaching Hospital, Lahore, adhere to evidence-based treatment protocols for PID, there are differences in diagnostic workup and follow-up. Regular training sessions and institutional guidelines are suggested to implement standardized management practices and enhance outcomes in patients.